PROSPEK BISNIS BANTEN : UPAYA MENGURANGI MENTAL KOMSUMTIF DAN KEMISKINAN DI BALI - NYOMAN SRI MULYANI (Purwadita : Jurnal Agama dan Budaya, 2017)
Upakara  is  part  of  yadnya  or  offerings  aimed  at  realizing  harmony.  The  ceremony  is also called Dewa Yadnya pujawali. Wali said that the philosophical symbolic meaning of offerings that are representative of the contents of the universe created by Ida Sang Hyang Widhi. Changes in lifestyle of the people of Bali from the agricultural industry has changed the order of Balinese life.  Activities  Bali  increasingly  complex  society  in  the  form  of  cultural  activities,  jobs,  and others so that women no longer Bali always worked together to make offerings or sajen, but had to  buy to  residents who are  experts  offerings.  There  are  several  factors  that  led  to  the  buying public offerings, namely (1) the factors bustle society, (2) factors of public knowledge, (3) social factors kemasyarakat, (4) factors of business opportunities keuntungam, (5) factors sradha bhaki, (6) the factors globalization, (7) the geographic factors and facilities, and (8) factor of chance.